Balancing “what matters to me” with “what matters to them”: exploring the legitimation process of environmental entrepreneurs - O'Neil, Isobel; Ucbasaran, Deniz (Elsevier, 2016)
We extend current knowledge on new venture legitimation by focusing on how environmental entrepreneurs enact their values and beliefs during the legitimation process and on the resultant business and personal consequences. On the basis of our longitudinal analysis of six cases studies we develop a staged process model of legitimation. Our findings suggest three novel insights. First, the entrepreneur’s (i.e. the legitimacy seeker’s) own values and beliefs are found to anchor initial decisions about how to gain legitimacy (the “what matters to me” stage) but are then toned down as attention shifts to gain legitimacy from diverse audiences (the “what matters to them” stage). Eventually, the entrepreneurs arrive at an approach that balances “what matters to me and them”. Second, we are able to explain how and why these changes in legitimation take place. The entrepreneurs learned to adapt their legitimation work by engaging in reflection and reflexivity about both the business and personal consequences of their work in each stage. Finally, we detail the significance of dissonance to this process as a trigger for changes in behavior. Overall, our three insights allow us to extend the notion of what a skillful legitimacy seeker might be.